If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(6p + 5) = -203 Reorder the terms: -7(5 + 6p) = -203 (5 * -7 + 6p * -7) = -203 (-35 + -42p) = -203 Solving -35 + -42p = -203 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -42p = -203 + 35 Combine like terms: -35 + 35 = 0 0 + -42p = -203 + 35 -42p = -203 + 35 Combine like terms: -203 + 35 = -168 -42p = -168 Divide each side by '-42'. p = 4 Simplifying p = 4
| 15a^2=13a+20 | | 15a^2=13a+20 | | 61=x+69 | | 12.5+g=18.1 | | 128=-6(5m+2)+2m | | 3/4x245 | | 11f=12f-5 | | 128=-6m(5m+2)+2m | | -8-6k=-7k-8(1+7k) | | 65=g+69 | | 60=x+67 | | -8(5+2a)=-5a+26 | | 12.5+5.25=g | | -128=-6(5m+2)+2m | | -128=-6(5m+2)+3m | | 100=13x+9 | | 1.5-8y=-30 | | 2x+8=3(x-7) | | -4m-4(7m-5)=-172 | | 12.5+5.25g= | | 7/9w-w=1/9 | | 32+4p=6(3p+1)-2 | | 7/(-7)-1 | | 12+5.25g= | | M=-3/4v | | 24+6r=2(6r+8)-5r | | 4(8n+3)-5=2(6n+8) | | 80=11x-8 | | 91=-7(x-7) | | 27-8y=4 | | 6(2+m)=12+6m | | -13=122+m |